The promise in Paul Ricoeur. A look from the teaching experience - Méndez del Portal, Rocío (2024)
This article addresses the topic of the promise from the perspective of Paul Ricoeur. It aims to analyze the importance and applicability of the constitutive components of personal identity –idem and ipse– in the teaching experience. In the development of the research, the promise, proposed by the French philosopher, is contrasted with the educational experience. In this sense, the ethical implications and the commitment derived from the responsibility assumed by the word given as a result of the relationship between educator and student are evaluated. It is concluded that the promise taken to the educational field implies an intersubjective relationship that requires being able to adapt to the challenges that may arise over time to sustain the given word.